The international handbook of Islamic banking and finance - Jackson-Moore, Elisabeth (Hawkhurst, Cranbrook, Kent : Global Professional Pub., 2009)
The book is a comprehensive, international guide covering the workings and details of Islamic banking and finance today.
Includes bibliographical references and index.
rua 05/11/13
Loans
Keywords: Banks and banking; Finance; Islamitische economie